Interactive Media Based on Gamification in Learning Fikih Chapter Thaharah Class 7 - Satria Rusydan Ilmawan; Cut Luluk Maskuroh; Nur’aini Fidaris Salamah; Roihan Arrosyid (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Purification learning, as part of basic Islamic jurisprudence, plays a crucial role in shaping students' religious understanding from an early age. However, conventional approaches to delivering material are often unattractive and unable to maintain students' motivation to learn optimally. This study aims to design interactive gamification-based learning media as an innovation in delivering purification material for seventh-grade students at MBS Kertek Wonosobo. This media is designed to provide a more enjoyable, competitive, and applicable learning experience through games such as levels, points, badges, and interactive quizzes. The media development process adapts the first two stages of the ADDIE model: needs analysis and media design. The study results indicate that students require media that can encourage active involvement and facilitate understanding of the concept of purification through a visual and interactive approach. This media design is made in the form of a branching quiz using interactive PowerPoint that presents purification questions, and is equipped with a point-based assessment system. Because this research is still in the design stage and has not been implemented, further research is needed to test its effectiveness and practical impact in Islamic Religious Education learning.